Expert reports on factory outlet center: A critical appraisal - Heinritz, Günter; Rauh, Jürgen (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
There is hardly a topic which has aroused as much controversial discussion over the last few years as factory outlet centres (FOCs) and attitudes towards them in spatial planning. An assortment of expert reports — in some cases conflicting in their findings and reflecting the goals and interests of the clients who commissioned them — have come to be a bone of contention both in public debate and before the courts. It is against this background that expert reports on FOCs have to be subjected to critical scrutiny. The main differences between these reports emerge in connection with the statements they contain on the evaluation of the range of goods on offer in FOCs and the potential for adjustment, on the definition of catchment areas, and on assessing the impacts of FOCs on existing shopping centres in the surrounding area.